The Effect of Total Quality Management Implementation on Operational Performance of MSMEs in Malang City - Jihan Nadia Marwa; Fien Zulkarijah; Triningsih Sri Supriyati (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This study aims to determine the partial and simultaneous influence of the dimensions of total quality management (TQM) implementation on the operational performance of MSMEs in Malang City and to find out what dimensions of TQM are considered to be dominant in influencing operational performance during the Covid-19 pandemic. This research was conducted on MSME Entrepreneurs in Lowokwaru District, Malang City with a total sample of 45 respondents. Collecting data using a questionnaire and Likert scale to measure the dimensions. The instrument test in this study uses validity and reliability tests, and the analysis method uses multiple linear regression analysis. The results showed that all dimensions of TQM had partial effect except the dimensions of Long-Term Commitment and Unity of Purpose. The simultaneous test proves that the dimensions of TQM have a simultaneous effect on operational performance. It is also known that education and training are dimensions of TQM implementation that have a dominant influence on operational performance